Impact of ischaemia-reperfusion cycles during ischaemic preconditioning on 2000-m rowing ergometer performance - Turnes, T.; de Aguiar, R. A.; de Oliveira Cruz, R. S.; Salvador, A. F.; Lisbôa, F. D.; Pereira, K. L.; Raimundo, J. A. G.; Caputo, F. (European Journal of Applied Physiology, 2018)
Purpose: Although ischaemic preconditioning (IPC), induced by cycles of transient limb ischaemia and reperfusion, seems to improve exercise performance, the optimal duration of ischaemia-reperfusion cycles is not established. The present study investigated the effect of ischaemia-reperfusion duration within each IPC cycle on performance in a 2000-m rowing ergometer test. Methods: After incremental and familiarization tests, 16 trained rowers (mean ± SD: age, 24 ± 11 years; weight, 74.1 ± 5.9 kg; VO2peak, 67.2 ± 7.4 mL/kg/min) were randomly submitted to a 2000-m rowing test preceded by intermittent bilateral cuff inflation of the lower limbs with three cycles of ischaemia-reperfusion, lasting 5 min (IPC-5) or 10 min (IPC-10) at 220 or 20 mmHg (control). Power output, VO2, heart rate, blood lactate concentration, pH, ratings of perceived exertion (RPE), and near-infrared spectroscopy-derived measurements of the vastus lateralis muscle were continuously recorded. Results: No differences among treatments were found in the 2000-m test (control: 424 ± 17; IPC-5: 425 ± 16; IPC-10: 424 ± 17 s; P = 0.772). IPC-10 reduced the tissue saturation index and oxy-haemoglobin concentration during exercise compared with control. The power output during the last 100-m segment was significantly lower with IPC-10. The IPC treatments increased the heart rate over the first 500 m and decreased the pH after exercise. No alterations were observed in VO2, blood lactate, or RPE among the trials. Conclusion: In conclusion, IPC does not improve the 2000-m rowing ergometer performance of trained athletes regardless of the length of ischaemia-reperfusion cycles.